El tratado secreto del Barón de Río Branco: la alianza entre Brasil y Ecuador, 1904 (Traducción) - Santos, Luís Cláudio Villafañe G. (2016)
It is almost unknown in Brazil and Ecuador historiographies the existence of a secret military treaty between the two countries, signed on May 5, 1904, directed against the territorial claims of Peru. The article examines a growing tension between Brazil and Peru, which fought over an area of 442,000 square kilometers in the Amazon. Ecuador also had undefined limits with Peru. At the initiative of the Barón de Rio Branco, a secret military alliance treaty between Brazil and Ecuador was signed. While this agreement was not ratified by the signatory countries, it was of utmost importance to force the Peruvian government to open negotiations with Brazil, which years later resulted in the boundary treaty between the two countries.